2002
DOI: 10.1007/s10350-004-7247-0
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Fibrin Glue vs. Conventional Treatment for Anal Fistula

Abstract: No advantage was found for fibrin glue over fistulotomy for simple fistulas, but fibrin glue healed more complex fistulas than conventional treatment and with higher patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
1
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(176 citation statements)
references
References 30 publications
6
154
1
15
Order By: Relevance
“…The present study did not show any incidence of faecal or gas incontinence in any of the treated patients as also in all the similar studies, especially in the studies of El shobaky et al, [21], Zmora et al, [8] and Lindsey et al, [19].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The present study did not show any incidence of faecal or gas incontinence in any of the treated patients as also in all the similar studies, especially in the studies of El shobaky et al, [21], Zmora et al, [8] and Lindsey et al, [19].…”
Section: Resultssupporting
confidence: 85%
“…If a failure occurs after 1 attempt, then the patient should be offered various surgical options. In few studies, healing rates of 25% (Zmora et al, [8]) and 80% (Lindsey et al, [19] were noticed, after regluing, probably because of some technical flaws during the first attempt. If the technique is standardized and a learning curve is achieved, there should be no reason for a patient of fistula in ano, to have any different result after regluing as compared to that in the 1 st attempt.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other authors have achieved higher rates of success in treatment of cryptoglandular fistulas (1,13,19,23) . In the largest published series to date, CINTRON et al (4) reported a healing rate for cryptoglandular fistulas of 63%, compared with 35% for fistulas of other etiologies, with a mean follow-up of 1 year.…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, some researchers reported that none of their patients developed anal incontinence [6,10,14,15].The small sample size is one of the limitations of some of these studies. Another limitation is the large number of low fistulae in both groups of patients because surgical treatment of a low fistula is unlikely to compromise continence and recurrence as recurrence is more common in high fistula.…”
Section: Discussionmentioning
confidence: 97%